1996
DOI: 10.1016/s0167-8140(96)01844-0
|View full text |Cite
|
Sign up to set email alerts
|

Combined preoperative irradiation and direct postoperative 5-fluorouracil without negative effects on early anastomotic healing in the rat colon

Abstract: Background and purpose: Preoperative irradiation with direct postoperative chemotherapy could benefit patients undergoing surgery for colorectal cancer. This study was designed to examine, in an experimental model, if such treatment is feasible without detrimental effects on early anastomotic healing. Material and methods:A colonic segment was irradiated (25 Gy) in 3 groups (n= 10 each) o f male Wistar rats. After 5 days, a colonic resection was performed with anastomotic construction; only the distal lim b co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Various outcomes have been reported in the studies investigating the effects of 5-FU on wound healing. 31,[37][38][39][40][41][42] Nonetheless, 5-FU is the cytotoxic agent of choice in colorectal cancer CT and has the characteristics of existing on the peritoneal surface for long term and passing into the portal circulation in high amounts. 42 In the present study we used 5-FU together with preoperative RT.…”
Section: Discussionmentioning
confidence: 99%
“…Various outcomes have been reported in the studies investigating the effects of 5-FU on wound healing. 31,[37][38][39][40][41][42] Nonetheless, 5-FU is the cytotoxic agent of choice in colorectal cancer CT and has the characteristics of existing on the peritoneal surface for long term and passing into the portal circulation in high amounts. 42 In the present study we used 5-FU together with preoperative RT.…”
Section: Discussionmentioning
confidence: 99%
“…Biert et al (29) reported no difference in bursting pressure when irradiation was applied 5 days before surgery. They found stenosis in spite of anastomosis rupture and this overhealing was compensated for by chemotherapy (28). A healing delay only occurred if irradiation was associated with hyperthermia (29).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still concerns about the healing of rectal anastomoses (17), which had led Minsky et al (18) to recommend a diverting stoma. Conflicting results were also reported in experimental studies using high and moderate doses of irradiation (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). Heupel et al (19) and Crowley et al (20) reported a good outcome of colon and small bowel anastomoses, respectively, using a single 500-cGy preoperative dose of irradiation in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…During the last 5 days of the irradiation schedule (days [16][17][18][19][20], 5-FU (Fluracedyl 1,000 mg; Pharmachemie, Haarlem, the Netherlands) was administered intraperitoneally through the left lower quadrant of the anterior abdominal wall using a 24 G cannula. Animals received daily either 20 or 10 mg/kg 5-FU.…”
Section: Rct (Days 4-20)mentioning
confidence: 99%
“…Several studies, clinical and experimental, have reported histological changes in the small intestine and colon after RT [13][14][15][16]. Animal studies investigating the influence of combined RCT on colonic anastomosis have yielded conflicting results [17,18]. A limited number of the experimental studies evaluated histologically the effect of preoperative RCT on colonic anastomotic healing.…”
Section: Introductionmentioning
confidence: 99%